Integration of IoT And WBAN for Remote Health Monitoring - Khan, Abdallah Sadurdeen (Universiti Teknologi PETRONAS, 2017)
This paper aims at improving remote health monitoring systems that involves Wireless Body Area Networks (WBANs). The limitations of WBANs are analysed and an integration with Internet of Things (IoT) is proposed. The WBAN limitations that IoT could potentially resolve are mainly in the aspect of communication capabilities, computation and memory. A comprehensive integration framework between the two (2) systems is established. The Galvanic Skin Response (GSR) signal is the physiological data sample extracted from the WBAN to test all aspects of the integration framework – Data Extraction, Data Analysis and Cloud computing. The platinum Shimmer Kit is adopted for the WBAN subsystem and IoT is implemented via a Raspberry Pi 3. A successful integration of both systems will result in patients reducing their dependency on doctors and hospitals for routine medical check-ups since the patients required physiological date can be accessed and monitored remotely.